2016
DOI: 10.1302/2058-5241.1.000010
|View full text |Cite
|
Sign up to set email alerts
|

Acute ankle sprain: conservative or surgical approach?

Abstract: Ankle sprains fall into two main categories: acute ankle sprains and chronic ankle instability, which are among the most common recurrent injuries during occupational activities, athletic events, training and army service.Acute ankle sprain is usually managed conservatively and functional rehabilitation failure by conservative treatment leads to development of chronic ankle instability, which most often requires surgical intervention.Enhancing the in-depth knowledge of the ankle anatomy, biomechanics and patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 59 publications
0
31
0
3
Order By: Relevance
“…Once the patient has painless full range of motion and strength, they may return to sport, typically between 6–12 weeks, depending on injury severity. 42 …”
Section: Lower Extremitymentioning
confidence: 99%
“…Once the patient has painless full range of motion and strength, they may return to sport, typically between 6–12 weeks, depending on injury severity. 42 …”
Section: Lower Extremitymentioning
confidence: 99%
“…Items are rated using a 5-point Likert scale, ranging from 1 (strongly disagree) to 5 (strongly agree). The m-RUQ total score is computed by adding the scores for each domain and dividing the result by the number of items tive measures [2], but many people end up developing chronic ankle instability and pain [5]. Chronic ankle instability (CAI) refers to the development of repetitive ankle sprains, instabilities of the ankle-joint complex [6], and persistent residual symptoms post-injury [7].…”
Section: Methodsmentioning
confidence: 99%
“…The ankle has been reported to be the most traumatized body part in sport injury literatures, accounting for 10-30% of all sport injuries [1]. Besides sporting world, ankle sprains are very much common in the general population [2]. Some studies have reported that 2-7 individuals are affected per 1000 in the general population each year [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Ankle sprain is one of the most common injuries in sports and general activities (Al-Mohrej and Al-Kenani, 2016a). Furthermore, around 20% of patients who suffer intense ankle sprain go on to develop functional ankle instability (FAI) due to lack of functional rehabilitation (Brown et al, 2008;Hopkins et al, 2009;Al-Mohrej and Al-Kenani, 2016b).…”
Section: Introductionmentioning
confidence: 99%